2017
DOI: 10.2147/ijgm.s141111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of toxicity from Amanita mushroom poisoning

Abstract: ObjectiveTo describe and analyze the clinical characteristics and outcome of amatoxin poisoning cases.MethodsWe performed a retrospective cohort study of amatoxin poisoning cases from Ramathibodi Poison Center Toxic Exposure Surveillance System, from May 2013 to August 2015.ResultsThere were 30 consultations with a total of 55 poisoning cases. Most cases were male and from the north-east region. Hepatitis, acute kidney injury, jaundice, and coagulopathy accounted for 74%, 46.3%, 44.7%, and 52.8% of the cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Also, silymarin can prevent the absorption of toxins into the hepatocytes by occupying the binding sites as well as by inhibiting many transport proteins at the cell membrane. The phalloidin‐transporting system, (which is involved into the incorporation of phallotoxin into the hepatocytes) belonging to the hepatocyte‐specific organic anion uptake transporters OATP2, is inhibited in a competitive way by silymarin with no influence on membrane fluidity (Trakulsrichai et al, ).…”
Section: Experimental Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, silymarin can prevent the absorption of toxins into the hepatocytes by occupying the binding sites as well as by inhibiting many transport proteins at the cell membrane. The phalloidin‐transporting system, (which is involved into the incorporation of phallotoxin into the hepatocytes) belonging to the hepatocyte‐specific organic anion uptake transporters OATP2, is inhibited in a competitive way by silymarin with no influence on membrane fluidity (Trakulsrichai et al, ).…”
Section: Experimental Pharmacologymentioning
confidence: 99%
“…However, uncontrolled trials and several case reports describe successful treatment with an intravenous silybin administration, even in the severely poisoned patients (Mengs, Pohl, & Mitchell, ). Empiric experience suggests the administration of 5 mg/kg silybin every 4 hr for 3–4 days after mushroom ingestion in association with N‐acetylcysteine and multiple‐dose activated charcoal (Karvellas et al, ; Trakulsrichai et al, ).…”
Section: Mushroom Poisoningmentioning
confidence: 99%
“…2,3 Most fatalities are due to amatoxin-containing species, which cause hepatotoxicity and fulminant liver failure. 2,3,[5][6][7] Rhabdomyolysis is a syndrome of mushroom poisoning that is described as either rapid or delayed onset myotoxicity. 2,3 Mushroom poisoning with delayed onset myotoxicity reported in literature is associated with ingestion of selected Tricholoma species, including T. equestre, 2,[8][9][10][11][12] and possibly T. terreum.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12]17 In some areas of Thailand, foraging for and consuming wild mushrooms are also popular, contributing to the incidence of mushroom poisoning in our country. 7 Besides amatoxin poisoning, myotoxic mushroom poisoning has significant or severe clinical effects. 21 Clinical data for myotoxic mushroom poisoning are limited.…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, silymarin has been shown to have regulatory actions on the permeability of the mitochondrial membrane and to increase cell membrane stability during xenobiotic injuries. 23 Silymarin also prevents the absorption of toxins by hepatocytes, 24 suggesting potential efficacy in the treatment of liver injuries induced by drugs or toxic substances. Schrieber et al 25 showed that the availability of silymarin and, consequently, its efficacy, varied with the type of liver disease.…”
Section: Introductionmentioning
confidence: 99%